Let $f:(0, \infty) \rightarrow R$ be a differentiable function such that $f'(x)=2-\frac{f(x)}{x}$ for all $x \in(0, \infty)$ and $f(1) \neq 1$. Then, |
$\lim\limits_{x \rightarrow 0^{+}} f'\left(\frac{1}{x}\right)=1$ $\lim\limits_{x \rightarrow 0^{+}} x f\left(\frac{1}{x}\right)=2$ $\lim\limits_{x \rightarrow 0^{+}} x^2 f'(x)=0$ $|f(x)| \leq 2$ for all $x \in(0,2)$ |
$\lim\limits_{x \rightarrow 0^{+}} f'\left(\frac{1}{x}\right)=1$ |
The function $f(x)$ satisfies the differential equation $\frac{d f(x)}{d x}+\frac{1}{x} f(x)=2$ .....(i) This is a linear differential equation with I.F. = $e^{\int \frac{1}{x} d x}=e^{\log x}=x$ Multiplying (i) by Integrating factor = x and integrating, we obtain $x f(x)=x^2+C$ $\Rightarrow f(x)=x+\frac{C}{x}$ $\Rightarrow f'(x)=1-\frac{C}{x^2}$ $\Rightarrow f'\left(\frac{1}{x}\right)=1-C x^2$ It is given that $f(1) \neq 1$. So, $C \neq 0$. ∴ $\lim\limits_{x \rightarrow 0^{+}} f'\left(\frac{1}{x}\right)=\lim\limits_{x \rightarrow 0^{+}}\left(1-C x^2\right)=1,$ $\lim\limits_{x \rightarrow 0^{+}} x^2 f'(x)=\lim\limits_{x \rightarrow 0^{+}}\left(x^2-C\right)=-C, $ and, $\lim\limits_{x \rightarrow 0^{+}} x f\left(\frac{1}{x}\right)=\lim\limits_{x \rightarrow 0^{+}} x\left(\frac{1}{x}+C x\right)=1$ Thus, option (a) is correct. We observe that for $C=1, f(x)=x+\frac{1}{x} \geq 2$. So, $|f(x)| \leq 2$ is not true. This can also be observed from the fact that $\lim\limits_{x \rightarrow 0^{+}} f(x) \rightarrow \infty$ for $C>0$. |